Sixty‐eight consecutive patients assessed for COVID‐19 infection: Experience from a UK Regional infectious diseases Unit. Issue 4 (8th April 2020) - Easom, Nicholas; Moss, Peter; Barlow, Gavin; Samson, Anda; Taynton, Thomas; Adams, Kate; Ivan, Monica; Burns, Phillipa; Gajee, Kavitha; Eastick, Kirstine; Lillie, Patrick J.
Abstract: Background: Assessment of possible infection with SARS‐CoV‐2, the novel coronavirus responsible for COVID‐19 illness, has been a major activity of infection services since the first reports of cases in December 2019. Objectives: We report a series of 68 patients assessed at a Regional Infection Unit in the UK. Methods: Between 29 January 2020 and 24 February 2020, demographic, clinical, epidemiological and laboratory data were collected. We compared clinical features between patients not requiring admission for clinical reasons or antimicrobials with those assessed as needing either admission or antimicrobial treatment. Results: Patients assessed were aged from 0 to 76 years; 36/68 were female. Peaks of clinical assessments coincided with updates to the case definition for suspected COVID‐19. Microbiological diagnoses included SARS‐CoV‐2, mycoplasma pneumonia, influenza A, non‐SARS/MERS coronaviruses and rhinovirus/enterovirus. Nine of sixty‐eight received antimicrobials, 15/68 were admitted, 5 due to inability to self‐isolate. Patients requiring admission on clinical grounds or antimicrobials (14/68) were more likely to have fever or raised respiratory rate compared to those not requiring admission or antimicrobials. Conclusions: The majority of patients had mild illness, which did not require clinical intervention. This finding supports a community testing approach, supported by clinicians able to review more unwell patients. Extensions of the epidemiological criteria for the case definition of suspected COVID‐19 lead to increased screening intensity; strategies must be in place to accommodate this in time for forthcoming changes as the epidemic develops.